In vitro and in vivo evaluation of porous alginate hydrogel containing retinoic acid for skin wound healing applications. (July 2022) - Nazarnezhad, Simin; Salehi, Majid; Samadian, Hadi; Ehtermi, Arian; Kasaiyan, Nahid; Khastar, Hossein; Abbaszadeh-Goudarzi, Ghasem; Kolarijani, Nariman Rezaei; Yeganehfard, Hodays; Ziaei, Heliya
The current study's main aim was to fabricate and evaluate alginate (Alg) hydrogel containing retinoic acid (RA) as wound healing materials. Different RA concentrations (2, 10, and 50% w/w) were incorporated into the hydrogel. The results showed that the prepared hydrogels had a porous structure with a pore size of 69.69 ± 22.1 µm for pure Alg hydrogel and 78.44 ± 27.8 µm for Alg/RA hydrogel. The swelling measurement showed that the hydrogels swelled up to 65% and the incorporation of RA reduced the degree of swelling . The in vitro studies confirmed the hemo- and biocompatibility of the Alg/RA 2% and increasing the RA concentration induced hemolysis and toxic effects. The animal studies showed that the lowest RA concentration resulted in the best treatment outcome while increasing the RA concentration suppressed the healing process. In conclusion, these results showed that RA induced wound healing process at low concentration, and the prepared hydrogel could be used as the wound healing materials.